Impact of the Stringent Stress Response on the Expression of Methicillin Resistance in Staphylococcaceae Strains Carrying mecA, mecA1 and mecC - Catarina Milheiriço; Alexander Tomasz; Hermínia de Lencastre (MDPI AG, 2022)
The acquisition of the resistance determinant mecA by Staphylococcus aureus is of major clinical importance, since it confers a resistant phenotype to virtually the entire large family of structurally diverse β-lactam antibiotics. While the common resistance determinant mecA is essential, the optimal expression of the resistance phenotype also requires additional factors. Previous studies showed that the great majority of clinical isolates of methicillin-resistant S. aureus (MRSA) have a heterogeneous resistant phenotype, and we observed that strains carrying methicillin genetic determinants other than mecA also produce similar heterogeneous phenotypes. All these strains were able to express high and homogeneous levels of oxacillin resistance when sub-inhibitory concentrations of mupirocin, an effector of the stringent stress response, were added to growth media. Our studies show that the gene gmk, involved in guanine metabolism, was one of the first genes to exhibit mutations in homoresistant (H*R) derivatives obtained through serial passages (with increasing concentrations of oxacillin) of the prototype mecC-carrying MRSA strain LGA251. All these observations led us to propose that a common molecular mechanism for the establishment of high and homogeneous oxacillin resistance must be present among isolates carrying different methicillin resistance determinants. In this work, we tested this hypothesis using whole-genome sequencing (WGS) to compare isogenic populations differing only in their degrees of oxacillin resistance and carrying various methicillin genetic determinants